2009
DOI: 10.1152/japplphysiol.91191.2008
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory interactions in patients with atrial flutter

Abstract: tory sinus arrhythmia (RSA) is generally known as the autonomically mediated modulation of the sinus node pacemaker frequency in synchrony with respiration. Cardiorespiratory interactions have been largely investigated during sinus rhythm, whereas little is known about interactions during reentrant arrhythmias. In this study, cardiorespiratory interactions at the atrial and ventricular level were investigated during atrial flutter (AFL), a supraventricular arrhythmia based on a reentry, by using cross-spectral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
2
5
0
Order By: Relevance
“…AV response curves in our patients extend these results, since they pointed out not only the decrease of AV CRs at higher atrial rates, but also the existence of a subtle structure of n:m coupling patterns between dominant n:1 coupling regions. As concerns pattern stability, the lower stability of AV coupling and the increased variability of ventricular response at higher atrial rate observed in our patients is consistent with previous studies in patients with atrial flutter (29,30) and AF (1,14). A decreased stability of AV coupling patterns was indeed observed during the transitions from slow to rapid atrial flutter forms (30), and an increased irregularity of ventricular interval series occurred at higher atrial rates in patients with AF and congestive heart failure (14).…”
Section: Discussionsupporting
confidence: 92%
“…AV response curves in our patients extend these results, since they pointed out not only the decrease of AV CRs at higher atrial rates, but also the existence of a subtle structure of n:m coupling patterns between dominant n:1 coupling regions. As concerns pattern stability, the lower stability of AV coupling and the increased variability of ventricular response at higher atrial rate observed in our patients is consistent with previous studies in patients with atrial flutter (29,30) and AF (1,14). A decreased stability of AV coupling patterns was indeed observed during the transitions from slow to rapid atrial flutter forms (30), and an increased irregularity of ventricular interval series occurred at higher atrial rates in patients with AF and congestive heart failure (14).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, our results showed ventricular irregularity to increase as a function of the atrial rate, with complex ventricular response occurring even with regular, but high-rate atrial activation. The increase of ventricular irregularity at higher atrial rate is consistent with previous studies in patients with atrial flutter (Masè et al 2009), paroxysmal AF (Masè et al 2015), and AF with congestive heart failure (Corino 2013), and can be explained in light of nodal factors. Indeed, an increase in atrial rate may induce a shift towards advanced levels of AV block, which are intrinsically instable and associated with increased contribution of concealed conduction (Langendorf 1965, Chorro 1991, Masè et al 2012.…”
Section: Populationsupporting
confidence: 90%
“…Nonetheless other extrinsic factors, such as respiration and autonomic tone, may influence the observed interactions. Respiration has been shown to modulate AFL rate and to combine with AV node filtering to produce complex patterns of ventricular intervals (Masè et al 2009). As well the direct influence of autonomic tone on AV conduction has been demonstrated in patients during normal sinus rhythm, atrial pacing and AF (Nollo 1994, Corino 2014).…”
Section: Populationmentioning
confidence: 99%
“…Furthermore, these oscillations are not abolished by complete autonomic blockade and have been reported in the transplanted heart (Bernardi et al, 1990(Bernardi et al, , 1989. Similarly, a MEF mechanism has been suggested to cause respiratory oscillations in the cycle length of human atrial flutter (Masè et al, 2009) that persist after autonomic blockade (Ravelli et al, 2008). In the intact human heart, atrial flutter rate also fluctuates in synchrony with cyclic variations in atrial volume secondary to ventricular contractions (Lammers et al, 1991;Ravelli et al, 1994), further supporting an interplay between cardiovascular mechanisms and electrophysiological changes mediated by MEF.…”
Section: Cardiovascular and Respiratory Oscillationsmentioning
confidence: 77%